(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The Present study aimed to perform a detailed in-vivo study of prepared baicalein (BCA) loaded hydrogel for wound healing effect and effect was compared with the marketed formulation. Prepared hydrogels were characterized and optimized already in previous study. Baicalein-loaded hydrogel (GG-GC-HGs) was prepared by using glycol chitosan gellan gum polymers. Prepared hydrogels were evaluated for wound healing effect using diabetic wound model (Streptozotocin induced) in rats. The wound healing effect was observed by measurement of wound contraction and biochemical estimation (Hydroxyproline, protein content and antioxidant assay) in the wound tissue after treatment. Histological examination of wound tissue was observed. Results of study showed that percent wound contraction of baicalein loaded GG-GC-HGs treated animal group showed a significant (p < 0.05) reduction after 10th day of treatment and healed completely on 18th day. Hydroxyproline and protein content were increased significantly with treatment of baicalein-loaded GG-GC-HGs and results were comparable with reference group (Hydroheal Gel) of animals. Antioxidant status was restored after treatment with BCA loaded GG-GC-HGs. The histological observation of wound tissues supported these results. In conclusion, baicalein loaded hydrogel showed prominent wound healing effect through increasing epithelialization, fibroblast proliferation and reducing oxidative stress in diabetic condition.